Research on oscillation characteristics of wind farm sending system based on participation factor - Qiu Peng; Song Jingen; Chen Qian; Zhou Wei; Xiong Bingyu; Tang Aihong (Frontiers in Energy Research, 2022)
The MMC-HVDC transmission system of wind farms has a very broad application prospect, but there is gradually growing major concern that the system is prone to broadband oscillation. And the mechanism of oscillation also remains to be clarified. In this article, based on the basic principle of eigenvalue analysis, the theoretical calculation equation of the quantitative evaluation index of the participation factor is deduced. The small-signal model of the MMC-HVDC transmission system for a wind farm is established. Combining with the case of 200 wind turbines connected to the grid, the eigenvalue analysis method is used to obtain the dominant oscillation mode of the system. The participation factors of 11 oscillation modes of the system are calculated to further analyze the relationship between the oscillation modes and the state variables in the MMC-HVDC transmission system of the wind farms. And the correlation between the participation factors of each oscillation mode, wind farm, and the MMC system is investigated, which laid a foundation for the formulation of broadband oscillation suppression strategies.